External Relations of Russian Border Regions - L. R. Rustamova (Vestnik MGIMO-Universiteta)
Despite de-globalization, which has become a trend in recent years, a high degree of interdependence between countries remains in the world, and the solution of global problems through international cooperation of subnational units is in demand. Intrastate regions affect interstate relations by strengthening their cultural, trade, and economic ties, often contributing to the intensification of interstate dialogue. The article looks for the primary factors and features of international activity of Russia’s border regions as territories located near foreign states and which have the most significant number of “points of contact.” It also tries to assess their impact on Russia’s foreign policy. The study shows that Russian regions have recently gained some independence in their external relations and managed to acquire all the features of influential non-state actors, according to the theory of actorness by Russet and Star. They have become integrated into a wide variety of international structures, where they can implement joint infrastructure projects with foreign regions and develop local self-government. Russian border regions become active on the international stage when they have common socio-economic and security problems, ethno-confessional, and cultural-linguistic affinity with the regions of neighboring states, and when the federal center uses their regions for important geopolitical factors for the foreign policy of the federal center. Building close ties based on cultural, linguistic, and ethnic affinity, the Russian regions perform a “compensating function,” making up for the lack of mutual understanding at the level of bilateral relations. They also act as “diplomatic agents” of the federal center in international organizations which promote local-level democracy. Regions also have the potential to build up Russia’s “soft power.” Although cross-border cooperation implies some costs, which the federal authorities try to reduce through legal regulation, it is still widely supported by federal governments.